2008 7th IEEE International Conference on Development and Learning 2008
DOI: 10.1109/devlrn.2008.4640796
|View full text |Cite
|
Sign up to set email alerts
|

Parental action modification highlighting the goal versus the means

Abstract: Abstract-Parents significantly alter their infant-directed actions compared to adult-directed ones, which is assumed to assist the infants' processing of the actions. This paper discusses differences in parental action modification depending on whether the goal or the means is more crucial. When demonstrating a task to an infant, parents try to emphasize the important aspects of the task by suppressing or adding their movement. Our hypothesis is that in a goal-crucial task, the initial and final states of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…These changes to the way that infants process different types of information might increase infants' attention to the physical properties of objects relevant to object function, induce development of motor activities related to object manipulation (e.g., reaching, manipulating, fingering), and motivate infants to increase their exploration of objects in their environment. Indeed, investigations of computer vision algorithms have shown that functional features of objects are visually salient, particularly when seen in events in which actors manipulate objects, even to a viewer (i.e., a computer vision algorithm) that cannot act on objects itself (Nagai & Rohlfing, 2008, 2009.…”
Section: Discussionmentioning
confidence: 99%
“…These changes to the way that infants process different types of information might increase infants' attention to the physical properties of objects relevant to object function, induce development of motor activities related to object manipulation (e.g., reaching, manipulating, fingering), and motivate infants to increase their exploration of objects in their environment. Indeed, investigations of computer vision algorithms have shown that functional features of objects are visually salient, particularly when seen in events in which actors manipulate objects, even to a viewer (i.e., a computer vision algorithm) that cannot act on objects itself (Nagai & Rohlfing, 2008, 2009.…”
Section: Discussionmentioning
confidence: 99%
“…Another interesting issue from a developmental perspective is to analyze different tasks as well as different teaching-learning scenarios. My hypothesis is that key points in a demonstrated action will be extracted differently depending on the goal-orientedness of the task and on the ability of learners [23]. Such analytical studies employing bottom-up architectures would contribute to uncovering human development.…”
Section: Discussionmentioning
confidence: 99%
“…The author has investigated parental scaffolding for infants' action learning as well as for robots' [18], [23]. The focus of this experiment, however, is on the evaluation of the proposed system rather than on the analysis of parental teaching.…”
Section: Object and Motion Associationmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigations in the field of parent-infant research [17], [18], which are partly based on a model proposed by [19] showed that parents modify their actions when teaching their children tasks, such as stacking cups. Parents start the interaction by highlighting and shaking the important object that is involved in the task and begin their demonstration when the child focuses on the object.…”
Section: A Attention-based Criterionmentioning
confidence: 99%